Depletion of ASK1 blunts stress-induced senescence in adipocytes. (1st January 2020) - Wueest, Stephan; Lucchini, Fabrizio C.; Haim, Yulia; Rudich, Assaf; Konrad, Daniel
ABSTRACT: Increasing energy expenditure via induction of browning in white adipose tissue has emerged as a potential strategy to treat obesity and associated metabolic complications. We previously reported that ASK1 inhibition in adipocytes protected from high-fat diet (HFD) or lipopolysaccharide (LPS)-mediated downregulation of UCP1 both in vitro and in vivo . Conversely, adipocyte-specific ASK1 overexpression attenuated cold-induction of UCP-1 in inguinal fat. Herein, we provide evidence that both TNFα-mediated and HFD-induced activation of p38 MAPK in white adipocytes are ASK1-dependent. Moreover, expression of senescence markers was reduced in HFD-fed adipocyte-specific ASK1 knockout mice. Similarly, LPS-induced upregulation of senescence markers was blunted in ASK1-depleted adipocytes. Thus, our study identifies a previously unknown role for ASK1 in the induction of stress-induced senescence.